2023
DOI: 10.3390/ma16196529
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Characteristics of Asphalt Concrete as an Impervious Core in Embankment Dams under Varying Temperatures and Stress States

Xiaoning Han,
Zaiqiang Hu,
Liangshu Yu
et al.

Abstract: To reveal the dynamic characteristics of asphalt core embankment dams (ACEDs), we carried out a dynamic triaxial experiment on hydraulic asphalt concrete (HAC) under different temperatures (T = 4 °C, 10 °C, 16 °C, and 22 °C) and stress states (Kc = 1.0, 1.2, 1.4, and 1.6; σ3 = 0.5, 0.6, 0.7, and 0.8 MPa). The results indicate that HAC’s maximum dynamic elastic modulus increased with decreasing temperature, increasing principal stress ratio, and increasing confining pressure. However, the damping ratio showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In many countries, lots of hydraulic structures are built in the alpine cold region; with low temperatures and frequent earthquakes, the dynamic mechanical safety performance of the RCHAC core wall has always been the concern of researchers. There have been many efforts to study the mechanical properties and failure mechanisms of RCHAC [ 2 , 3 , 4 , 5 , 6 ]; the majority of these, however, ignored the effect that size has on mechanical properties, while many studies showed that the size of the specimen has a significant effect on the mechanical properties of heterogeneous concrete-like materials [ 7 , 8 , 9 , 10 , 11 ]. Therefore, another noteworthy aspect is the influence of the specimen size on the mechanical properties and failure mechanisms in the mechanical research of HAC.…”
Section: Introductionmentioning
confidence: 99%
“…In many countries, lots of hydraulic structures are built in the alpine cold region; with low temperatures and frequent earthquakes, the dynamic mechanical safety performance of the RCHAC core wall has always been the concern of researchers. There have been many efforts to study the mechanical properties and failure mechanisms of RCHAC [ 2 , 3 , 4 , 5 , 6 ]; the majority of these, however, ignored the effect that size has on mechanical properties, while many studies showed that the size of the specimen has a significant effect on the mechanical properties of heterogeneous concrete-like materials [ 7 , 8 , 9 , 10 , 11 ]. Therefore, another noteworthy aspect is the influence of the specimen size on the mechanical properties and failure mechanisms in the mechanical research of HAC.…”
Section: Introductionmentioning
confidence: 99%